A fluorescent bisboronic acid compound that selectively labels cells expressing oligosaccharide Lewis X. Issue 12 (15th June 2015) - Gao, Xingming; Zhu, Mengyuan; Fan, Haiying; Yang, Wenqian; Ni, Weijuan; Karnati, Vishnu V.R.; Gao, Shouhai; Carson, John; Weston, Brent; Wang, Binghe
Graphical abstract: Abstract: Two fluorescent diboronic acid compounds (6a and6b ) with a dipeptide linker were synthesized as potential sensors for cell surface saccharide Lewis X (Le X ). Compound6a with a dipeptide (H-Asp-Ala-) as the linker was found to selectively label CHOFUT4 cells, which express Le x, at micromolar concentrations, while non-Le x -expressing control cells were not labeled.